Advances in Toxoplasma gondii Vaccines: Current Strategies and Challenges for Vaccine Development - Chu, Ki-Back (Vaccines (Basel), 2021)
Toxoplasmosis, caused by the apicomplexan parasite Toxoplasma gondii, is one of the most damaging parasite-borne zoonotic diseases of global importance. While approximately one-third of the entire world’s population is estimated to be infected with T. gondii, an effective vaccine for human use remains unavailable. Global efforts in pursuit of developing a T. gondii vaccine have been ongoing for decades, and novel innovative approaches have been introduced to aid this process. A wide array of vaccination strategies have been conducted to date including, but not limited to, nucleic acids, protein subunits, attenuated vaccines, and nanoparticles, which have been assessed in rodents with promising results. Yet, translation of these in vivo results into clinical studies remains a major obstacle that needs to be overcome. In this review, we will aim to summarize the current advances in T. gondii vaccine strategies and address the challenges hindering vaccine development.